Hipócrates líric a l'Humanisme catalá - Redondo, Jordi (1996)
Hippocratic quotations in the Middle Ages have been usually restricted to a small number of treatises, namely Aphorisms, Prognostic and Regimen of acurate diseases, which constituted some kind of canon. Moreover, the immediat source for Hippocrates was not in many cases a Latin or Arabic translation, but the version of Galen, Plinius, and the like. In spite of this, Ausiàs March made in his poetical work some very exact quotations of Hippocratic texts (Nature of man, Humours). Moreover, we must take into account a noteworthy fact, since the first Humanistic Age was not interested at all in the Hippocratic science, as the extant work of Petrarca can testify.
Keywords: Hipócrates; Petrarca, Francesco, -- 1304-1374; March, Ausiàs, -- ca. 1397-1459